The First Case Report of Ectopic Hepatic Tissue in a Guinea Pig. (25th January 2021) - Kimura, Tohru; Inaka, Kengo
Abstract : Ectopic hepatic tissue is an extremely rare developmental abnormality in human beings. Although this lesion is likewise rare in veterinary medicine and there were sparse reports in several species such as dogs, cats, cows, and calves, we incidentally encountered ectopic hepatic tissue in a guinea pig. In the case of guinea pigs, we report for the first time the occurrence of ectopic hepatic tissue implanted in the gallbladder. The healthy guinea pig remained asymptomatic, and its macroscopic findings also showed no abnormalities. Hematological examinations exhibited moderate decreases in white cell counts, hemoglobin concentrations, and packed cell volume ratio. Serum biochemical examinations showed decreases in total protein and albumin and increases in glucose levels, alkaline phosphatase, lactate dehydrogenase, creatine kinase, and γ -glutamyl transpeptidase. There were slight changes in electrolytes (Cl, Ca, and Mg) and inorganic phosphorus, indicating minor deviations from physiologic ranges. An increase in TBIL concentrations was not found in this examination. Histopathological examination revealed the presence of normal hepatic structures (hepatocytes and hepatic cords) within the wall of the normal gallbladder. The vascular and bile duct structures and portal triads were not observed in the ectopic hepatic tissue. In conclusion, this microectopic hepatic tissue in a guinea pig was characterized by the embedded structures of hepatic tissues, without foreign body reaction.